A review on gut microbiota and migraine severity: a complex relationship - Noha M. Gamil; Rana M. Ghorab; Reham Z. Elsadawy; Nada M. Khadrawy; Mohamed Abdelhamid; Khalid A. Ismael; Omar A. Mohamed; Mohamed M. Ata; Habiba T. Jalal; Joumana E. Zeidan; Reem T. Rashed; Riham A. El-Shiekh (Inflammopharmacology, 2026)
The gut-brain axis plays a vital role in migraine pathophysiology. Studies highlight reciprocal interactions between the central nervous system and the gastrointestinal tract. Previous research suggests that factors such as gut microbiota profiles, inflammatory mediators, neuropeptides, serotonin pathways, stress hormones, and nutritional substances influence this interaction. The pathophysiology of migraine has been linked to changes in the gut-brain axis, which affects migraine severity and frequency. Additionally, dietary approaches, including the ketogenic diet, vitamin D supplementation, omega-3 intake, probiotics, and weight loss plans, have shown promising effects in reducing migraine symptoms by positively impacting the gut microbiota and the gut-brain axis. Understanding these connections could lead to novel therapeutic strategies for effectively managing migraines. It is worth noting that research highlights several innovative treatments for migraine, such as Zelirex and Cevimide, implantable devices like Cefaly and Revilion, and new effective routes of administration for Sumatriptan. Finally, patients’ perspectives and concerns were thoroughly discussed, with a focus on future directions in the migraine-gut axis research.